Characteristics and prognosis of synchronous multiple primary lung cancer after surgical treatment: A systematic review and meta‐analysis of current evidence. (10th December 2020) - Tie, Hongtao; Luo, Jun; Shi, Rui; Li, Zhenhan; Chen, Dan; Wu, Qingchen
Abstract: Background: This study aims to quantitatively summary the characteristics of synchronous multiple primary lung cancer (sMPLC), postoperative mortality, long‐term prognosis, and prognostic effects of potential clinical parameters in patients with sMPLC after surgery. Methods: PubMed and Embase databases were systematically searched to identify studies that explored the prognosis of patients with sMPLC after surgery. Results: Fifty‐two studies with 3486 participants were included, and clinical characteristics were quantitatively summarized. The pooled proportion of sMPLC in lung cancer was 2.0% (95%CI, 1.6%–2.5%) with an increasing trend over time, and postoperative mortality was 1.4% (95%CI, 0.5%–2.7%) with a decreasing trend over time. The 5‐year survival rate was 44.9% (95%CI, 37.4%–52.6%) and all long‐term survival rates showed increasing trends over time. Poor long‐term prognosis was observed in both limited resection (HR = 1.357, 95%CI, 1.047–1.759, p = 0.0210) and pneumonectomy (HR = 2.643, 95%CI, 1.539–4.541, p = 0.0004) by comparison of anatomical resection. Other clinical parameters of age, gender, smoking status, FEV1, and lymph node metastasis significantly impacted the long‐term prognosis (all p < 0.05). Conclusions: The proportion of sMPLC in lung cancer and 5‐year survival rate are increasing, while postoperative mortality is decreasing trend over time. Lobectomy should be preferred, while pneumonectomy should be avoided for sMPLC. Age, gender, FEV1, smoking, tumor size, surgical methods, and lymph node status are prognostic factors for sMPLC. Considering the heterogeneity and publication bias, these findings should be treated with caution. Abstract : The incidence of sMPLC increases over time, with an estimated incidence of 2.0%. The postoperative mortality decreases, while the long‐term survival rate increases over time.